2021
DOI: 10.1039/d1ta03205d
|View full text |Cite
|
Sign up to set email alerts
|

Carbonate formation lowers the electrocatalytic activity of perovskite oxides for water electrolysis

Abstract: The study of oxide electrocatalysts is often complicated by the formation of complex and unknown surface species as well as the interaction between the catalysts and common support materials. Because...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…[16,39] Thus, when too many oxyanions are present, they will block the OER active sites. [23,40,41] This competition is consistent with the observation that the addition of oxyanions to the electrolyte first leads to an improvement of the OER activity (see following paragraphs), but after a certain concentration (in the order of magnitude of 0.1 M) the overpotential increases. [15,16] In this regard, it is worth mentioning that anodic potentials can increase the local concentration of (oxy)anions in the (near-)surface area of the electrode, as oxyanion migration into the double-layer can take place to compensate the build-up positive charge on the electrode surface.…”
Section: àsupporting
confidence: 88%
See 1 more Smart Citation
“…[16,39] Thus, when too many oxyanions are present, they will block the OER active sites. [23,40,41] This competition is consistent with the observation that the addition of oxyanions to the electrolyte first leads to an improvement of the OER activity (see following paragraphs), but after a certain concentration (in the order of magnitude of 0.1 M) the overpotential increases. [15,16] In this regard, it is worth mentioning that anodic potentials can increase the local concentration of (oxy)anions in the (near-)surface area of the electrode, as oxyanion migration into the double-layer can take place to compensate the build-up positive charge on the electrode surface.…”
Section: àsupporting
confidence: 88%
“…Density functional theory (DFT) calculations revealed that the adsorption energy is often negative (e.g., −1.9 eV for SeO 4 2− on NiOOH) [15] and occurs at the same transition metal sites where the OER intermediates are adsorbed (Ni preferred to Fe) [16, 39] . Thus, when too many oxyanions are present, they will block the OER active sites [23, 40, 41] . This competition is consistent with the observation that the addition of oxyanions to the electrolyte first leads to an improvement of the OER activity (see following paragraphs), but after a certain concentration (in the order of magnitude of 0.1 M) the overpotential increases [15, 16] .…”
Section: The Effect Of Surface‐adsorbed Oxyanionssupporting
confidence: 73%
“…This enhanced material control with atomically smooth catalyst surfaces comes at the cost of a minimized contact area between catalyst and electrolyte, limiting the technological relevance of epitaxial systems. But such atomically controlled model systems have emerged as an ideal platform to identify structure-function-relationships at the atomic level, a prerequisite for advanced design rules ( Risch et al, 2013 ; May et al, 2015 ; Scholz et al, 2016 ; Gunkel et al, 2017 ; Eom et al, 2018 ; Bak et al, 2019 ; Liu et al, 2019 ; Weber et al, 2019 ; Baeumer et al, 2021a ; Baeumer, 2021 ; Baeumer et al, 2021b ; Wan et al, 2021 ) and offering to finally overcome the materials challenge imposed by the activity-stability dilemma.…”
Section: Atomistic Understanding Of Activity and Degradation Relies O...mentioning
confidence: 99%
“…241 In case of OER, the presence of carbonate was found to decrease the catalytic activity of LaNiO 3 by formation of carbonates which altered the chemical environment of active sites. 242 This may be generally applicable to other transition metal based OER catalysts.…”
Section: Impact Of Impurities In Awes and Aemwesmentioning
confidence: 98%